Gas chromatographic characterization of mycobacteria: analysis of fatty acids and trifluoroacetylated whole-cell methanolysates. - Larsson, L (1976)
Mycobacterium avium, M. bovis strain Bacillus Calmette-Guerin (BCG), M. kansasii, and M. tuberculosis were studied by gas-liquid chromatography. Methylated fatty acids of the mycobacterial lipids and trifluoroacetyl (TFA) derivatives of whole-cell methanolysates were analyzed. Both the fatty acid and the TFA chromatograms showed reproducible differences between the various mycobacteria studied. Chromatograms from different strains of one and the same species showed negligible differences. Fatty acid methyl esters and TFA methyl glycosides are probably the main constituents of the TFA chromatograms. TFA derivatives are easily prepared and the method provides a potential tool for species indentification of mycobacteria.